The Effect Of Blood Microplastic Particle Count On Corticosterone Hormone Level In Rattus Norvegicus Strain Wistar - I Made Aindrea Mahaputra Widiastawa; Patricia Gabrielle Tjipta Joewana; Yudhiakuari Sincihu; Shella Morina; Henry Ricardo Handoyo (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Microplastics, particularly Low-Density Polyethylene (LDPE), are environmental pollutants that can enter the body through oral exposure and potentially accumulate in the bloodstream. The presence of microplastics in systemic circulation is suspected to trigger physiological stress responses through activation of the hypothalamic–pituitary–adrenal axis. This study aimed to determine the effect of the number of microplastic particles in the blood on corticosterone hormone levels in Rattus norvegicus Wistar strain rats. This study employed an experimental design with a control group and treatment groups that received oral exposure to LDPE microplastics for 28 days. The number of microplastic particles in the blood was examined using light microscopy and polymer identification was confirmed using FTIR, while corticosterone levels were measured using the ELISA method. The results showed an increase in the number of microplastics in the blood following exposure, accompanied by elevated corticosterone levels as an indicator of physiological stress. This study recommends further investigation into the long-term effects of microplastics on the endocrine system and their implications for human health.